Influence of open innovation variables on the competitive edge of small and medium enterprises - Ismael Cristofer Baierle; Guilherme Brittes Benitez; Elpidio Oscar Benitez Nara; Jones Luis Schaefer; Miguel Afonso Sellitto (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The purpose of this study is to identify how open innovation variables influence the competitive capability of manufacturing small and medium enterprises (SMEs) in a regional territory in Southern Brazil. The research method is a survey of 67 SMEs in Southern Brazil that provided data for an ordinary least squares (OLS) regression model encompassing seven innovation variables and five competitiveness constructs. The results indicate that most innovation initiatives have a low impact on creating a competitive edge in the surveyed companies. The most remarkable positive impacts are (i) technology trends influencing the shop floor productivity, (ii) flexibility influencing internal aspects, and (iii) customer satisfaction and innovative ideas and customized supplies influencing the market orientation. The study also reports that innovation processes are not safe from failures. Some ill-defined innovation initiatives may jeopardize the competitive edge.
Keywords: 650; open innovation; SMEs; competitiveness; emerging country; innovation management; regression analysis